Development of human-guided robot system using kinect sensor - Teo, Siew Hwi (2018)
As technologies are getting more and more advanced nowadays, people is increasingly reliant on robots for many purposes. There are many different types of commercial or household robots available in the market now. Different robots serve different purposes depending on requirements needed. Sony SCARA (Selectively Compliance Articulated Robot Arm) is one of them and will be used in this project.